Influence of Board Diversity on Firm Performance and Sustainability in Kenya - Wairimu, Florence (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to examine the influence of board diversity on firm performance and sustainability. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: diversity on corporate boards, whether in terms of gender, ethnicity, age, or cultural background, has consistently shown positive correlations with financial performance metrics, innovation outputs, ethical governance practices, and corporate social responsibility efforts. The study suggests that diverse boards are better equipped to navigate challenges, capitalize on opportunities, and enhance stakeholder engagement. Unique Contribution to Theory, Practice and Policy: Resource Dependence Theory, Agency Theory & Institutional Theory may be used to anchor future studies on Influence of Board Diversity on Firm Performance and Sustainability. Organizations should prioritize inclusive board recruitment practices that actively seek out diverse candidates based on gender, ethnicity, age, skills, and cultural backgrounds. This proactive approach ensures that boards reflect the diversity of their stakeholders and leverage a broader range of perspectives to drive innovation, resilience, and sustainable practices. Boards and senior management teams should invest in diversity training and education programs that promote awareness, sensitivity, and inclusion. Policymakers should consider enhancing regulatory guidelines that encourage transparency and accountability in board diversity disclosures. Clear reporting requirements on board composition, diversity metrics, and diversity initiatives can incentivize organizations to prioritize diversity as a strategic imperative and promote greater board diversity across industries and sectors.